PATHOGENETIC METHODS OF PREVENTING PATHOLOGY OF PARTURITION AND POSTPARTUM PERIOD AND TREATMENT OF COW OVARIES HYPO-FUNCTION, MASTITIS AND ENDOMETRITIS - Dovgopol, V. F.; Panasova, T. G. (Scientific Progress & Innovations, 2020)
High effectiveness of environmentally friendly “Selegumate” and “Sanobite” preparations developed at the Department of Surgery and Obstetrics of Poltava State Agrarian Academy to prevent retention of after-birth, postpartum endometritis and for treatment of cow ovarian hypo-function, mastitis and endometritis has been established. “Selegumate” is a sterile 0.5 % solution of sodium humate with adding sodium selenite, which forms an organic complex with salts of humic acids. Administered parentrally, “Selegumate” stimu-lates metabolism and increases the body's overall resistance, which normalizes the functions of the whole organism, and the reproductive system in particular, and improves its preparation for parturition and the physiological course of the postpartum period. “Sanobite” was created by us based on Poltava bischofite, by adding aerosil, novocaine and some other substances to it. When applied externally, “Sanobite” has anti-inflammatory, immune stimulatory, general tonic and adaptogenic effects, as well as inhibits micro-flora growth. In order to prevent retention of afterbirth “Selegumate” was administered to pregnant cows 30 and 15 days before the expected parturition and after it – subcutaneously, in the area behind the shoulder blade, at a dose of 1 ml per 100 kg of live weight. For the treatment of cow ovarian hypo-function, “Selegumate” was administered twice, with an interval of 10 days, subcutaneously, in the area behind the shoulder blade, at a dose of 1 ml per 100 kg of live weight. The second injection of “Selegumate” was made to cows, which did not show sexual arousal after the first injection. Thus, as a result of the administering “Selegumate”to a significant number of cows, the frequency of retention of afterbirth decreased by 5.5 times, the disease of acute postpartum endometritis – 3.8 times, 86.5 % of cows with anaphrodisia due to ovarian hypo-function restored sexual cycling and were fertilized. “Sanobite” was applied by rubbing in the skin of the affected quarter and teats of cows suffering from mastitis for 5 minutes once a day. The therapeutic efficacy of “Sanobite” at cow subclinical mastitis was 91.3 %, serous mastitis – 93.9 %, catarrhal acute mastitis – 95.8 %, chronic mastitis – 91.8 %. “Sanobite” is also recommended for the treatment of cow postpartum endometritis. The treatment of such cows was conducted by injecting “Sanobite” into the uterus at a dose of 50 ml. A therapeutic effect of “Sanobite” was up to 85.7 %. A simple effective method of diagnostics and treatment of cow subclinical endometritis, which ensures up to 80 % of fertilization from the first insemina-tion, is proposed for production.